Associação entre composição corporal, equilíbrio e mobilidade de idosos com 80 anos ou mais - Dos Santos, Vanessa R. [UNESP]; Christofaro, Diego G.D. [UNESP]; Dos Santos, Lionai L. [UNESP]; Gomes, Igor C. [UNESP]; Codogno, Jamile S. [UNESP]; Júnior, Ismael F. Freitas [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Study design: cross-sectional study. Objective: The objective of this study was to analyze the association between body composition, mobility and balance of elderly aged 80 years or older. Methods: The sample consisted of 123 elderly aged 80 and 95 years (83.2 ± 2.7 years) with 78 women (83.2 ± 2.9 years) and 45 men (83.2 ± 2, 4 years) residing in the city of Presidente Prudente - SP. Assessment of body composition was made by absorpiometria dual energy X-ray (DXA). The mobility and balance were assessed by means of tests of speed walking, and static balance lower limb strength. For statistical analysis we carried out the chi-square test, the software used was SPSS (13.0) and the significance level was set at 5%. Results: In males, those with higher performance in the functional tests showed higher percentages of muscle mass (MM) (35.6%) compared to lower performance (15.6%), p = 0.026. In the female group, the elderly with higher performance on tests showed higher bone mineral density (BMD) values (30.8%) compared with those with lower performance (20.5%) p = 0.041. Conclusion: MM for elderly males and BMD for females were the components of body composition that is associated with functional capacity.
Association between body composition, balance and mobility of elderly aged 80 years or older
Keywords: Aged, 80 and over; Body Composition; Mobility limitation; Postural balance; aged; body composition; body equilibrium; bone density; computer program; dual energy X ray absorptiometry; female; functional status; human; male; mobilization; muscle mass; muscle strength; performance; urban population; walking